Design and modelling of eco-friendly CH3NH3SnI3-based perovskite solar cells with suitable transport layers - Mottakin M.; Sobayel K.; Sarkar D.; Alkhammash H.; Alharthi S.; Techato K.; Shahiduzzaman M.; Amin N.; Sopian K.; Akhtaruzzaman M. (MDPI, 2023)
Copper oxides; Defects; Efficiency; Electron transport properties; Hole mobility; Lead compounds; Perovskite solar cells; Tin compounds; Tungsten compounds; Absorber layers; Amphoteric defects; Defect tolerance; Design and modeling; Eco-friendly; Hole transport materials; Maximum Efficiency; SCAPS-1D; Tolerance limits; Transport layers; Perovskite